SENTRA MEBEL SEBAGAI DESTINASI WISATA DENGAN PENDEKATAN ARSITEKTUR REGIONALISME DI JUWIRING, KLATEN - Fitria Khairanisa; Hadi Setyawan; Ahmad Farkhan (Universitas Sebelas Maret Surakarta, 2016)
The design background of Furniture Center at Juwiring is due to many of furniture craftmen that spread over in Juwiring. There is no center place to make furniture exhibition at Juwiring, it makes craftsmen have difficulty in marketing, and so do the consumer that have difficulty in search for information of furniture from Juwiring. The issue of design are: how to appear the image of a building that has a characteristic of Juwiring to be an attractive tourism destination at Juwiring. The method used is Defamiliarisasi method from Architectural Regionalism theory. The analysis design begins with gathering the potential of characteristic Juwiring, then decomposing to architectural building components. The result are design concept of furniture centers with facilities and infrastructure as a tourism destination. The concept of the building shows the characteristic of Juwiring which comes from the decomposition potential forms around Juwiring like joglo, pendhapa, Juwiring’s umbrella, and Prambanan. Keywords: Appearance Building, Juwiring’s Characteristic, Furniture Craftsmen at Juwiring, Regionalism Architecture, Tourism Destination.